2021
DOI: 10.1021/acs.inorgchem.0c03617
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide Supermolecular Transformers Induced by K+ and CO2

Abstract: The transfer of configuration information from supramolecular helices is a ubiquitous phenomenon in nature. DNA and proteins often change their helical structure in response to particular external stimuli and can activate important related events through sophisticated mechanisms. Attempts to create artificial multiple-stranded helicates that can adjust the configuration under external stimuli have also met with limited success. Using a simple ligand, we now show multiple-stranded lanthanide helicates that tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…4B(e) and (f)). Although many coordination hosts that can fix CO 2 by binding with carbonate have been reported, 95–102 the newly formed strong metal–oxygen interactions make these hosts unable to be reused. Thus, tube 1-Zn represents a rare coordination host that can catalyze CO 2 conversion like carbonic anhydrase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4B(e) and (f)). Although many coordination hosts that can fix CO 2 by binding with carbonate have been reported, 95–102 the newly formed strong metal–oxygen interactions make these hosts unable to be reused. Thus, tube 1-Zn represents a rare coordination host that can catalyze CO 2 conversion like carbonic anhydrase.…”
Section: Resultsmentioning
confidence: 99%
“…Further experiments showed that after removal of CO 3 2encapsulated by cavity, the tube 1-Zn can be regenerated and reused (Figure 4B e-f). Although many coordination hosts that can fix CO 2 by binding with carbonate have been reported, [95][96][97][98][99][100][101][102] the new-formed strong metal-oxygen interactions make these hosts cannot be reused. Thus, tube 1-Zn represents a rare coordination host that can catalyze CO 2 conversion like carbonic anhydrase.…”
Section: Co 2 Fixation Promoted By Coordination Tubesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been interested in the construction of novel high-nuclearity clusters and the determination of the structure–activity relationship of these lanthanide complexes. ,, To controllably prepare a supramolecular nanocage based on heterometallic complex and exploit the application of the coordination cage in catalysis, an unusual and discrete 3d–4f metallacage, [Zn 2 Er 4 (H 2 L ) 4 (NO 3 )­Cl 2 (H 2 O)]·NO 3 · x CH 3 OH· y H 2 O ( Zn 2 Er 4 ), was synthesized by the introduction of a semirigid and nonsymmetric bridging ligand (H 5 L ) with rich metal-chelating sites, which could effectively fix more lanthanide ions and coordinate with transition-metal ions via the self-adjustment of different coordination atoms. The 3d–4f Zn 2 Er 4 cage possesses a quadruple-stranded structure, and all ligands wrap around open spherical space within the core (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Between them, helicates can be considered very promising candidates that can be precisely designed to exhibit inherent bioactivity. The term "helicate" is referred to a particular class of self-assembled metallosupramolecular compounds, in which conveniently designed ligands wrap around two or more metal ions and form a double stranded helix [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%